PROEJA: entre currículos e identidades - MORENO, Sandra Antonielle Garcês (2012)
This research has as its theme the PROEJA: between curriculum and identities. We sought to examine whether the effectiveness of the PROEJA s school curriculum in the Campus Centro Histórico into IFMA, the multiple identities of individuals who comprise the audience of this type are being considered, paying attention to the connections between educational practices, cultural representations and social. It is a field research that was conducted from a quantitative and qualitative methodological approach. It involved a literature search of authors that underlie the analysis, with regard to adult education were essential studies of Paulo Freire (1996, 2005, 2008), Leoncio Smith (2002, 2007), Moacir Gadotti and José Eustaquio Romão (2008), Dante Henrique Moura (2010), among others, and Legislations (BRAZIL 1996, 2000, 2005, 2006), highlighting the PROEJA Base Documents (2006 and 2007); studies on Curriculum Antonio Flavio Moreira (1990, 1997 , 2003), Gimeno Sacristan (2000)) and Tomaz Tadeu da Silva (2009) were significant; since Identities collaborated on studies of Zygmunt Bauman (2005), Stuart Hall (2006), Homi Bhabha (2007) and Nestor Canclini (2008) . Was used, although the application of questionnaires with students and teachers, and interviews the Educational Sector Campus Historical Center, for data collection concerning the design and execution of the curriculum in that campus. It is understood that the study enabled the understanding that as the PROEJA can be established as a state policy for adult education, based on a curriculum whose bases are the identities of students and the operating conditions met, can contribute considerably to remedy this great social debt that the country has with young people and adults who for various reasons have not completed basic training and not having a quality professional education.